BAHASA ASING YANG MEMPENGARUHI GAIRAIGO PADA WEBSITE THE MULIA - Ni Kadek Nennytha Armayanthi; Ni Wayan Meidariani; Ladycia Sundayra (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2023)
Gairaigo is a type of Japanese vocabulary that generally comes from European countries. Gairaigo is used in the tourism sector because in Japanese there is no appropriate equivalent to describe terms in the world of tourism and hospitality that can explain precisely and facilitate the delivery of information. The data source used is The Mulia website. This study aims to describe the origin of the language of gairaigo used in The Mulia website. The data collection technique used in this research is the listen and note method. Data analysis methods and techniques used in this study were qualitative with descriptive methods, with informal data presentation. The results of this study indicate that 256 data were found gairaigo data, with 245 data from English, 7 data from French, 1 data from Dutch, 1 data from German, 1 data from Spanish, and origin of the Finnish language as much as 1 data. The data used in this study are 11 data with language origins from France, the Netherlands, Germany, Spain, and Finland.